Low‐Cost and High‐Efficiency Solar‐Driven Vapor Generation Using a 3D Dyed Cotton Towel. Issue 9 (22nd May 2019) - Yang, Yudi; Sui, Yujin; Cai, Zaisheng; Xu, Bi
Abstract: Solar‐driven vapor generation is a promising method to mitigate freshwater shortage and water contamination. However, most of the current highly efficient solar evaporators suffer from low robustness, tedious preparation procedures, and high cost. In this study, an easy‐to‐manufacture, low‐cost, and high‐reliability solar‐driven evaporator is designed using a black cotton towel with a hollow conical shape. The reactive dye molecules diffuse into the cotton and form strong covalent bonds with the fiber after dyeing, which firmly fixes light‐absorbing materials on the substrate. The looped pile structure of towels and hierarchical structure of yarns enable the evaporator enlarged surface area. The hollow conical shape of the cotton towel can effectively suppress the heat loss to the environment without compromising light absorption. The 3D vapor generator exhibits an evaporation rate of 1.40 and 1.27 kg m −2 h −1 for pure water and saline water, respectively. Meanwhile, this towel‐based solar‐driven evaporator exhibits a promising antifouling property as well as superior reusability and provides a reliable pathway in dealing with realistic waters, such as seawater and dyeing sewage. Therefore, the low‐cost, solar‐driven water evaporation system offers a complementary approach for high‐efficiency vapor generation and water purification in practical application. Abstract : An inexpensive, scalable, and efficient solar‐driven vapor generator is prepared by placing a conical black cotton towel on a floatable polystyrene foam with the cotton stripes dipping into the water. This 3D vapor generator exhibits a promising antifouling property as well as superior reusability and provides a reliable pathway in dealing with realistic waters, such as seawater and dyeing sewage.